2018
DOI: 10.29252/jhehp.4.3.8
|View full text |Cite
|
Sign up to set email alerts
|

The Netosis Formation of HL-60 Cell Differentiated to Neutrophil-Like Cells by LPS

Abstract: Journal homepage: www.zums.ac.ir/jhehp Background: Neutrophils are the most abundant white blood cells in humans. Recently, a novel strategy called the formation neutrophil extracellular traps (NETs) was described. NETs is a new strategy for pathogen response. This study focused on whether LPS induced NETs release in vitro in the HL60 cell line. Methods: In this study, the HL60 cell line was used for culture and DMSO for induction and differentiation. Flow cytometry was used to evaluate CD11b in the differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Notably, dHL-60 cells have previously been used to study NETosis in vitro. 31,56 Consistent with those prior reports, R848 induced NETosis in dHL-60 cells (Figure S7). Furthermore, we observed that pS9L inhibited NETosis and that siRNA knockdown of Siglec-9 (encoded by SIGLEC9) or SHP-1 (encoded by PTPN6) abrogated the effect of pS9L (Figures 3e, S8 and S9).…”
Section: ■ Introductionsupporting
confidence: 92%
“…Notably, dHL-60 cells have previously been used to study NETosis in vitro. 31,56 Consistent with those prior reports, R848 induced NETosis in dHL-60 cells (Figure S7). Furthermore, we observed that pS9L inhibited NETosis and that siRNA knockdown of Siglec-9 (encoded by SIGLEC9) or SHP-1 (encoded by PTPN6) abrogated the effect of pS9L (Figures 3e, S8 and S9).…”
Section: ■ Introductionsupporting
confidence: 92%
“…The HL-60 line is a promyelocytic leukemia that can be differentiated into a neutrophil-like cells (dHL-60) using all-trans retinoic acid (ATRA, 100 nM) and dimethylsulfoxide (DMSO, 1.25% v/v), which have previously been used to study NETosis in vitro. 31,56 We observed that R848 induced NETosis in dHL-60 cell's ( Figure S7). Furthermore, we observed that pS9L inhibited NETosis and that siRNA knockdown of Siglec-9 (encoded by SIGLEC9) or SHP-1 (encoded by PTPN6) abrogated the effect of pS9L (Figure 3e, S8, S9).…”
Section: Tlr-7/8 Agonist R848 Induces Netosis Of Primary Neutrophils mentioning
confidence: 88%
“…The HL-60 line is a promyelocytic leukemia that can be differentiated into a neutrophil-like cells (dHL-60) using all-trans retinoic acid (ATRA, 100 nM) and dimethylsulfoxide (DMSO, 1.25% v/v), which have previously been used to study NETosis in vitro. 31,56 We observed that R848 induced NETosis in dHL-60 cell's (Figure S7). Furthermore, we observed that pS9L inhibited NETosis and that siRNA knockdown Sera and plasma from COVID-19 patients have been shown to be sufficient to induce NETosis of neutrophils isolated from healthy donors in vitro.…”
Section: A Siglec-9 Agonist Inhibits Tlr-7/8-induced Netosis Via Shp-1mentioning
confidence: 88%